Perancangan Media Pembelajaran Aqidah Akhlak Dengan Smart Apps Creator Berbasis Mobile Apps di MTI Canduang - Sari, Nita; Derta, Sarwo; Musril, Hari Antoni; Darmawati, Gurnita (INTEK : Jurnal Informatika dan Teknologi Informasi, 2023)
The problems in this study are based on the results of observations and interviews that the author conducted, first, the teaching teacher still uses printed book media, second, the teacher still uses the lecture method, third, the teacher has not used technological media as a support. Meanwhile, students said they felt bored and quite difficult to understand the material for teaching morals because teachers still did not use technology-based me-dia as a support. Based on this, the researcher is interested in conducting research by providing a technological approach, namely producing the design of learning media for Aqidah Akhlak with smart apps creators based on mobile apps at MTI Canduang. This study uses the Research and Development (R&D) method with the DDD-E development model. Media development using the DDD-E model consists of Decide, Design, Develop, Evaluate. The results of the product test that the author did obtained a validity test from 6 validators obtained a value of 0.82 with a valid category, practicality test from 2 students obtained a value of 0.92 with a very high category, and the effectiveness test of 15 students obtained a value of 0.84 with high effectiveness category.